Application of Infinite Memory Structure and Finite Memory Structure Filters for Electric Motor System - Soo Kim, Pyung; Jun Kwon, Seok (International Journal of Engineering and Technology, 2018)
In this paper, both IMS and FMS filters are applied for the estimation filtering of electric motor systems. Firstly, the electric motor system and its state-space model is described, Secondly, IMS and FMS filters are briefly introduced and compared. These two filters are represented by the summation form and use the rotational speed as the output measurement unlike the existing work. Thirdly, comprehensive simulation works are performed for both certain system and temporarily uncertain system. Simulations results show that the FMS filter can be better than the IMS filter for the temporarily uncertain system. It is also shown that there can be the trade-off between two filtering performance indices, estimation error and tracking speed in terms of the memory length.Â Â